Field simulation and structure optimization of the air conveying system in air assisted sprayer based on computer fluid dynamics - XU Yimeng; ZHU Xiaowen; LIU Zhijie; HU Yaohua; GU Fang (浙江大学学报. 农业与生命科学版)
To shorten research and development cycle and reduce cost, an air conveying system in the air assisted sprayer was designed and optimized by computer fluid dynamics (CFD) technology. Based on the principle of minimizing the energy loss and vortex of airflow and maximizing the uniformity of flow distribution, we determined the optimal structure and specific parameters of the bellows. In addition, to adapt to different growth periods and different types of orchards by adjusting the height and inclination of the system according to the canopy shape, we explored the influence of air velocity and installation angle on air-flow field using CFD simulation calculation and test, and simulated the distribution of flow field in the sprayer. Then we established the linear model between spray height and nozzle inclination after obtaining the relationship between airflow distance and airflow velocity (as the wind transmission distance increased, the wind speed gradually decreased, and the decreasing amplitude also decreased). The results showed that when the nozzle inclination was greater than 85° or less than 40°, there was little effect on the change of airflow field; when the nozzle inclination was 40°-85°, the spraying height was basically linear with the nozzle inclination with the increase of nozzle inclination. This study provides a theoretical basis for the automation of simulation spray.